Tough Questions on Faith and Development: A Reflection - Jayakaran, Ravi; Slimbach, Richard (Christian Relief, Development, and Advocacy: The Journal of the Accord Network, 2024)
The following is a response by Ravi Jayakaran, president of Medical Ambassadors International, to the three questions Richard Slimbach poses on faith and development in his article “Asking Tough Questions About Transformational Development,” published in this journal in the summer of 2023 (Slimbach 2023). A follow up comment by Slimbach appears at the end. Both of these contributions were part of a webinar on June 27, 2023 discussing that article; the rest of the webinar content, consisting of two other responses and discussion around them, are published this issue as well. The full recording of the webinar can be found at https://vimeo.com/844345288/e970fe8826?share=copy. The specific questions to which Ravi Jayakaran responds are: How important is a Christian conversion experience to the formation of deep morality and optimal human development? And how valid is the claim that “transformed persons inevitably transform society?” The “capabilities” approach asserts an alternative moral basis for human development than that typically associated with the “transformational” paradigm. In what ways do they contradict, complete, or even correct each other? Why should religion be taken seriously by secular development practitioners?